Thermal inkjet printing of copper tetrasulfonated phthalocyanine (CuTsPc) as a semiconducting layer on flexible MIS capacitors - Gomes,Tiago Carneiro (2014)
Thermal inkjet-printing of copper tetrasulfonated phthalocyanine (CuTsPc) films containing polyvinyl alcohol (PVA) plasticizer were used to fabricate flexible metal-insulator-semiconductor (MIS) capacitors using anodic aluminum oxide (Al2O3) as the insulating layer. The Al2O3 layer and printed CuTsPc+PVA films were characterized individually and in a MIS structure by electrical impedance spectroscopy. Capacitance-frequency and capacitance-voltage measurements revealed distinct contributions from CuTsPc and PVA on the device electrical response. From these measurements the semiconductor charge carrier mobility, ∝, of 1.22x10- 4 cm² V- 1 s- 1 and the doping density, N A, of 3.1x10(16) cm- 3 were calculated. It was observed a low-frequency electrical response, which was attributed to diffusional processes within the printed film arising from Na+ ions dissociated from the CuTsPc molecule. A simple equivalent circuit model was proposed to take this effect into account. Finally, the results shown here demonstrate the possibility to produce flexible organic electronic devices exploiting the semiconducting properties of water-soluble CuTsPc molecules using low-cost commercial printers.